Lafora Disease: A Review of Molecular Mechanisms and Pathology - Verhalen, Brandy; Arnold, Susan; Minassian, Berge A. (Neuropediatrics, 2018)
Lafora's disease is a neurodegenerative disorder caused by recessive loss-of-function mutations in the EPM2A (laforin glycogen phosphatase) or EPM2B (malin E3 ubiquitin ligase) genes. Neuropathology is characterized by malformed precipitated glycogen aggregates termed Lafora bodies. Asymptomatic until adolescence, patients undergo first insidious then rapid progressive myoclonus epilepsy toward a vegetative state and death within a decade. Laforin and malin interact to regulate glycogen phosphorylation and chain length pattern, the latter critical to glycogen's solubility. Significant gaps remain in precise mechanistic understanding. However, demonstration that partial reduction in brain glycogen synthesis near-completely prevents the disease in its genetic animal models opens a direct present path to therapy.
Keywords: Lafora Disease; progressive myoclonus epilepsy; polyglucosan body